An analytical study of Cryptography and Steganography technique for robust Security and integrity of the data - Donga, Hitendra; Atkotiya, Kishor (International Journal of Computer Sciences and Engineering, 2025)
As we all know the data security is the biggest concern for all the domains and it has very deep impact on the data and its security. Here in this paper we have tried to carry out the analytical study of the different cryptography and steganography technique which is used to maintain the integrity of the data. Any type of cover object can be taken that may be text, image or video to embed the secret information. In this paper a brief analysis of different image stegnography techniques and their comparison is done